Monocyte PGE2 secretion in Hodgkin's disease and its relation to decreased cellular immunity. - Passwell, J (1983)
The secretion of PGE2 from monocytes of newly diagnosed patients with Hodgkin's disease (HD) was compared to that of patients in remission, who were not receiving either chemotherapy or radiotherapy, and normal controls. We found that monocyte monolayers of some patients, both newly diagnosed and those in remission, secreted markedly elevated levels of PGE2. The lymphocyte proliferative response to PHA was increased to a similar extent in both newly diagnosed patients and those in remission when cultured in the presence of indomethacin. PGE2 concentrations in the medium of mononuclear cultures correlated with the lymphocyte proliferative response to PHA (P less than 0.05). However, no correlation of monocyte PGE2 production with decreased E rosette forming lymphocytes, anergy or clinical stage could be demonstrated. We suggest that PGE2 secretion by monocytes is indicative of an 'activated' state of these cells. It is, however, unlikely that PGE2 is the only molecular species responsible for the decreased cellular immune function in HD. 'Activated' monocytes may be part of the immune response in this disease and may be responsible for the decreased cellular immunity.